COCONUT PLANTATION FIRES: A REVIEW OF DRIVERS, IMPACTS, AND MITIGATION STRATEGIES - Felixtianus Eko Wismo Winarto; Diki Bima Prasetio; Bambang Hari Priyambodo (PT. Radja Intercontinental Publishing, 2026)
Fires in coconut plantations, especially on tropical peatlands, cause serious environmental and economic problems. While most studies focus on oil palm, this literature review summarizes the causes, impacts, prevention methods, and restoration strategies specific to coconut plantations. The review shows that fires are mainly triggered by cheap land-clearing practices and the accumulation of dry wastes like husks and fronds, which become highly flammable during El Niño droughts and over-drainage. These fires cause direct palm mortality, reduce crop yields for up to three years, cause peat subsidence, and generate dangerous smoke haze that harms public health. To prevent these fires, strategies like proper water management, community involvement, and satellite or drone monitoring are essential. For post-fire recovery, maintaining the surviving coconut canopy and using coconut fiber as mulch offer cost-effective ways to restore soil and biodiversity. In conclusion, managing fires requires a combination of better waste management, water control, and active community participation.